Constitutional design and the Brazilian judicial review: remarks about strong and weak-form review in the Brazilian Federal Supreme Court - Marco Antonio Loschiavo Leme de Barros (Revista Opinião Jurídica, 2017)
This paper discusses the constitutional design model of judicial review established in the 1988 Brazilian Federal Constitution through the classification model of strong and weak judicial review forms, generally applied to the Commonwealth countries. Since the end of the military dictatorship in the late 1980s, Brazil has been following a strong judicial supremacy with a hybrid judicial-review system concentrated very much in the Federal Supreme Court. Nevertheless, this paper argues that at the structural level Brazil’s constitutional design could be understood to operate in a weak-form judicial review, where the National Congress is granted the final word on constitutional matters in some situations. This conclusion is reached by analyzing some constitutional provisions and rulings. Despite the fact that Congress rarely overrides – in a responsive manner – the Brazilian Federal Supreme Court’s judicial review decisions due to political costs and agenda commitments, I argue that Brazil’s weak-form can be exemplified to some extent by highlighting the effects of two different and original constitutional actions: the indirect and concrete judicial review by the writ of injunction (mandado de injunção), to protect fundamental rights, and the direct and abstract judicial review by the declaration action of unconstitutionality by omission (ação declaratória de constitucionalidade por omissão). Both legal actions transfer to the legislator the final word about constitutional issues and some empirical evidence indicates that during the 1990s the Court had a self-contained performance regarding revision power in light of constitutional omissions cases. Finally, the major goal of this paper is to enter into dialogue with the literature of the weak-form judicial review and to encourage a new discussion of application and debate of the model. After all, in an optimal constitutional rule-of-law design, not only do judges play an important role, but the participation of the legislature and executive branch are also required.